A realization of the uncertainty uniformity principle in a grouting model - Demchuk, M.; Saiyouri, N. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2012)
A method of a realization of the uncertainty uniformity principle in grouting model calculations is described.